2001
DOI: 10.1007/s11745-001-0751-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel sphingophosphonolipid head group 1‐hydroxy‐2‐aminoethyl phosphonate in Bdellovibrio stolpii

Abstract: Members of the bacterial genus Bdellovibrio include strains that are free-living, whereas others are known to invade and parasitize larger Gram-negative bacteria. The bacterium can synthesize several sphingophospholipid compounds including those with phosphoryl bonds as well as phosphonyl bonds. In the present study, the dominant sphingophosphonolipid component was isolated by column chromatography, and the long-chain bases, fatty acids, and polar head groups were identified by thin-layer and gas-liquid chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
43
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 38 publications
1
43
0
Order By: Relevance
“…Bacteriovorax stolpii UKi2 was obtained from the American Type Culture Collection (ATCC 27,052) and cultured axenically in 0.3% yeast extract and 1% bactopeptone as described previously [29].°Cell°density°as determined by Abs 660 nm indicated that cultures grown in the enriched medium yielded ϳ28% higher bacterial numbers than when grown with 0.3% yeast extract alone. Standing cultures were incubated at 30°C until they reached stationary phase.…”
Section: Bacterial Culture and Extraction Of Lipidsmentioning
confidence: 99%
See 3 more Smart Citations
“…Bacteriovorax stolpii UKi2 was obtained from the American Type Culture Collection (ATCC 27,052) and cultured axenically in 0.3% yeast extract and 1% bactopeptone as described previously [29].°Cell°density°as determined by Abs 660 nm indicated that cultures grown in the enriched medium yielded ϳ28% higher bacterial numbers than when grown with 0.3% yeast extract alone. Standing cultures were incubated at 30°C until they reached stationary phase.…”
Section: Bacterial Culture and Extraction Of Lipidsmentioning
confidence: 99%
“…The cell pellet was extracted for total lipids using chloroform (CHCl 3 ):methanol (MeOH)°(2:1,°vol/vol)° [29]°or°by°the°method°of°Bligh and°Dyer° [36].…”
Section: Bacterial Culture and Extraction Of Lipidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bdellovibrio is characterized by the unique predatory behavior by which it invades various other larger gram-negative bacteria and grows as a parasite in the intraperiplasmic space of the prey (46,47,56,57). Bdellovibrio contains a phosphono ceramide, which carries the characteristic head group 1-hydroxy-2-aminoethyl phosphonate (62). The bacteria listed above are exceptions in gram-negative bacteria in that they lack lipopolysaccharides and instead contain a large amount of sphingolipids, including glycosphingolipids (33,(67)(68)(69)(70)72); most gram-negative bacteria contain lipopolysaccharides, the major pathogenic glycolipids of the outer membrane.…”
mentioning
confidence: 99%